Critical Role of Cysteine-Rich Protein 61 in Mediating the Activation of Renal Fibroblasts - Liu, Hang; Zhao, Long; Zhang, Jisheng; Li, Chenyu; Shen, Xuefei; Liu, Xuemei; Jiang, Wei; Luo, Congjuan; Wang, Yanfei; Che, Lin; Xu, Yan (Frontiers in Physiology, 2019)
Objective To explore the role of cysteine-rich protein 61 (Cyr61) in ischemic renal fibrosis and renal fibroblasts. Methods (1) The rat model of renal fibrosis was established after ischemia-reperfusion acute renal injury (IR-AKI). We detected the renal function by biochemical test, evaluated the fibrosis by Masson staining, and detected the expression of Cyr61 by western blotting. (2) Bioinformatics technique was adopted to analyze the expression of Cyr61 in activated renal fibroblasts. (3) Normal rat kidney fibroblast cells (NRK-49F cells) with over-expression of Cyr61 (Cyr61+) and low-expression of it (Cyr61--) were established by plasmid transfection. Then part of cells were activated by TGF-β1 and NRK-49F cells were divided into control group, activated group, Cyr61+/Cyr61-- group and Cyr61+/Cyr61-- activated group. The expression of Cyr61 and fibrosis related factors (Col1α1, Col3α1, MMP9, MMP13) were ascertained by PCR and western blotting. Cell proliferation was discovered by CCK8 method, cell cycle was analyzed by flow cytometry, and the transcription of cell senescence related factors (P53, P21, Rb, P16) were ascertained by PCR method. Results (1)In the process of fibrosis after IR-AKI, the area of collagen fiber was most obviously at AKI 1W, while the Cyr61 protein was at the lowest level at AKI 1W. (2) Gene chip analysis showed that the expression of Cyr61 was decreased in renal fibroblasts after IR. (3) Compared with control group, Cyr61+ group expressed less Col1α1 or Col3α1, as well as more MMP9 and MMP13. At the same time, the proliferation of Cyr61+ group decreased and cells in G1 phases increased with more transcription of P53, P21 and Rb (all P<0.05). Compared with activated group, the results of Cyr61+ activated group were similar to the above. The above effects of low expression group were just opposite. In addition, there was no difference in the transcription of P16 among these groups (P>0.05)． Conclusions Cyr61 may not only inhibit the fibrotic phenotype of fibroblasts, but also inhibit proliferation by promoting fibroblasts arrest in G1 phase through the P53/P21/Rb interrelated cell senescence pathway, subsequently affecting the process of ischemic renal fibrosis.